Relationship of Zakat and Waqf to Poverty and Inequality: Bibliometrics Analysis - El Ashfahany, Afief; Multazam, Muhammad Qodrat; Ahmed, Shahumeel; Ab Rahman, Muhamad Radzuan; Apriantoro, Muhamad Subhi (Suhuf: International Journal of Islamic Studies, 2025)
This paper explore the research of the role of zakat and waqf on poverty and inequality by using bibliometric analysis as content analysis. Based on bibliometric analysis, from 174 articles, Sadeq (2002), Ab Rahman et al., (2012); Ali & Hatta (2014), Haneef et al., (2015), and Rahman & Dean (2013) are the top 5 journals with the most citations of and are considered as supporters of the creation of other journals that research on zakat and waqf which effect on poverty and social inequality. In addition, this study also uses content analysis using top 20 articles. Several points of content analysis results show that poverty alleviation through zakat can be maximized through good zakat governance and regulator collaboration. On the other hand, the role of waqf can be maximized through the use of technology. And finally, the collaboration of zakat and waqf plays a role in poverty alleviation, inequality and sustainable development.